Young Generation's Contribution in Building a Halal Industry Ecosystem in Indonesia - Julianti, Ayu; Rafidah, Rafidah; Alawiyah, Rabiyatul; Kanahaya, Shofy Nindia; Martina, Rizqina; Husen, Muhamad; Maulana, Akbar (PT Inovasi Pratama Internasional, 2024)
The younger generation in Indonesia plays a pivotal role in building the ecosystem of the halal industry, with a focus on technological innovation, entrepreneurship, Sharia financial education, and business ethics. This research, using a qualitative method, aims to discuss the development of the halal industry in Indonesia and the strategic role of the younger generation. The research findings indicate Indonesia's significant potential in the halal industry based on the majority Muslim population, natural resources, and government support. The younger generation's role in innovation and social responsibility is key to the growth of the halal industry, positioning Indonesia as a global leader in halal product consumption